Asymmetry, cytoarchitectonic morphology and genetics associated with Broca’s area in schizophrenia - Zimmermann, Saskia; Sakreida, Katrin; Bludau, Sebastian; Camilleri, Julia Ann; Hoffstaedter, Felix; Pelzer, Dominique I.; Aleman, André; Brückner, Torsten Ulf; Derntl, Birgit; Frank, Elmar; Frodl, Thomas; Fuentes-Claramonte, Paola; et al. (Nature Mental Health, 2024)
A common hypothesis on the etiopathology of schizophrenia is that the failure of segregation of right from left hemisphere functions is a core deficit in psychosis. It has even been proposed that schizophrenia symptoms in general may reflect a hemispheric ‘dominance failure’ for language and that the corresponding predisposition is genetic. Here, we show that reduced asymmetries of cytoarchitectonic Broca’s subareas link to the degree of specific psychopathology and that specific gray matter reductions of subareas are related to a cognitive and a negative subtype of schizophrenia. Gene expression analyses indicate an upregulation of the MET gene in these particular areas, which has been implicated in neurodevelopment as well as neurocognition and influences the risk for schizophrenia. Our integrative findings suggest that variations of MET are associated with distinct structural alterations at the subregional level in key language regions, which may contribute to development of specific psychopathology in schizophrenia.
Gesehen am 11.02.2026